Intention to Use Online Food Delivery Service in Malaysia among University Students - Rae Hooi; Tang Kin Leong; Lai Hui Yee (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Online food delivery (OFD) service becomes more prevalent in Malaysia. OFD has advantages for consumers where it entices many people to utilise it in their daily life. Instead of purchasing food from a physical, consumers can purchase food through online platform and use the delivery service. In the era of information technology (IT), people from all walks of life are able to order food with one click away from their devices. This has lightened much work especially for busy working consumers. This research aimed to investigate the consumers’ intention to use online food delivery service in Malaysia. A total of 290 online questionnaires were received for data analysis. The finding of the study indicates that time saving and prior online purchase experience are major predictors of OFD. However, the perceived usefulness and price saving were found insignificant. Restaurants should improve their OFD service to attract more consumers. Convenience of information stored enable consumers to reuse OFD service